A dual‐polarized wideband gain enhancement Fabry–Perot antenna by adopting a wedge‐shaped phase correcting structure. Issue 12 (28th September 2022) - Yu, Yun‐Kai; Liu, Zhi‐Ming; Zhou, Hui‐Lin; Chen, Wei; Wang, Zheng‐Hai; Wang, Yu‐Hao
Abstract: A dual‐polarized wideband Fabry‐Perot (FP) antenna based on a wedge‐shaped phase correcting structure (WPCS) is proposed. The antenna adopts a wideband dual‐linear polarized slot‐coupled antenna as a primary antenna, and adopts a single‐layer FSS structure with positive reflection phase gradient characteristics as a partially reflecting surface (PRS) of the FP resonator, to optimally excite the FP cavity resonances within a wide operating band. Moreover, a small circular metal patch array is printed on the other side of the FSS unit structure. The small circular patch array effectively increases the reflection amplitude without changing the positive reflection phase gradient characteristics of the PRS, which improves the FP antenna gain. In addition, a highly graded WPCS is loaded in the resonant cavity to properly compensate the phase between different reflection paths inside the resonant cavity, which enhances the gain of the FP antenna in a wide band. Finally, the measured peak gains of the FP antenna under the excitation of Port 1 and Port 2 are 16.0 dBi and 15.89 dBi, respectively, and the gain enhancement can reach up to 3 dBi after loading the WPCS. The measured 10‐dB impedance‐matching operating bandwidth of dual‐polarized common coverage is 14.08 to 16.45 GHz (15.53%).